Risk factors for red blood cell alloimmunization in polytransfused patients - Svetlana Jović Lacković; Almira Ćosićkić (Medicinski glasnik, 2026)
Aim: Alloimmunization depends on the type of the erythrocyte antigen, as well as the number of transfused doses of blood and recipient factors reflected in genetic and immunological status, comorbidities and therapy. The aim was to determine the frequency and type of antierythrocyte antibodies, to examine the correlation between the number of transfused doses and the frequency of antibodies, as well as the influence of recipient factors on the prevalence of antierythrocyte antibodies in polytransfused patients. Methods: A retrospective study was conducted in the Department of Pretransfusion Testing and Blood Product Therapy at the Polyclinic for Transfusion Medicine of the University Clinical Center Tuzla. The data of patients who received two or more doses of red blood cell concentrate, the frequency of antierythrocyte antibodies, as well as dose and patient factors including age, sex, comorbidity and therapy that influenced alloimmunization were analyzed. Results: The highest percentage of patients developed the anti-E (23%), anti-C (11%) and anti-K (17%) antibodies. The recipient factors that have shown to be positive predictors for the development of antierythrocyte antibodies were: surgical bleeding (OR=3.74) and autoimmune diseases (OR=2.3). The probability that patients will not develop antierythrocyte antibodies was more pronounced in oncological patients (1/OR=7.14), as well as in patients with iron supplementation (1/OR=2.22) and antihypertensive therapy (1/OR=2.32). Conclusion: The results emphasize the importance of pretransfusion testing, illuminate the positive and negative effects of frequent transfusions, and propose strategies for improving transfusion therapy with a focus on the benefits of phenotyping erythrocytes for Rh and Kell antigens.
Keywords: antierythrocyte antibodies; pretransfusion testing; transfusion